A first course in differential equations with applications - Zill, Dennis G., 1940- (Prindle, Weber & Schmidt series in mathematics, 1989)
This proven and accessible book speaks to beginning engineering and math students through a wealth of pedagogical aids, including an abundance of examples, explanations, "Remarks" boxes, definitions, and group projects.